Negative recency, randomization device choice, and reduction of compound lotteries - Kim Kaivanto; Eike Benjamin Kroll (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2011)
We report an experiment in which subjects are not indifferent between real-money lotteries implemented with randomization devices that are equivalent under the Reduction Axiom. Instead choice behavior is consistent with subjective distortion of conditional probability, and this persists in treatment conditions that control for (i) computational limitations and (ii) possible confounding by ratio bias.
urn:nbn:de:swb:90-228610
Keywords: D81; C91; 330; reduction of compound lotteries; negative recency effect; gambler's fallacy; law of small numbers; randomization devices; instruments and materials; design of experiments; St. Petersburg paradox